Plurilocular tomato varieties trial, at Goiânia, in the rainy season - Sonnenberg, Peter Ernst; Filgueira, Fernando Antônio Reis (Pesquisa Agropecuaria Brasileira, 2014)
Fifteen plurilocular tomato (Lycopersicum esculentum) varieties, Floradel F.M., Floradel L.B.T., Tropi-gro, Tropic, Floralou, Manalucie, 2003 D-2 DI-DBK, Híbrido Sekaiichi F-1, Maçã de Ibirité, L-352, Porter's Pride, Foremost E-21, Firebird, Grand Prix and Royal Ace, were compared during the hot and rainy season of 1970/71, at Goiânia, State of Goiás, Brazil. The variety Tropi-gro was the only one with determinate growth, all the other varieties were indeterminate and were pruned to two stems and staked. The Sekaiichi F-1 Hybrid ranked first in yielding large, well-shaped marketable fruits, over 200 grams, followed closely by Tropic, without significant difference between them. Tropic is somewhat more subject to Open Locule (Catface) injury than Sekaiichi. Floradel F.M., Floralou, Floradel L.B.T. and L-352 were also considered good varieties.